2020
DOI: 10.1016/j.omtm.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-CSF AAV9 and AAVrh10 Administration in Nonhuman Primates: Promising Routes and Vectors for Which Neurological Diseases?

Abstract: The identification of the most efficient method for whole central nervous system targeting that is translatable to humans and the safest route of adeno-associated virus (AAV) administration is a major concern for future applications in clinics. Additionally, as many AAV serotypes were identified for gene introduction into the brain and the spinal cord, another key to human gene-therapy success is to determine the most efficient serotype. In this study, we compared lumbar intrathecal administration through cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 53 publications
6
68
0
Order By: Relevance
“…These approaches will not target all cell types equally. For example, studies in non-human primates have demonstrated that intravenous administration of AAV9 in juvenile non-human primates predominately transduces glia (19,33) while direct administration into the cerebral spinal fluid (CSF) improves delivery to neurons (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches will not target all cell types equally. For example, studies in non-human primates have demonstrated that intravenous administration of AAV9 in juvenile non-human primates predominately transduces glia (19,33) while direct administration into the cerebral spinal fluid (CSF) improves delivery to neurons (34).…”
Section: Resultsmentioning
confidence: 99%
“…These approaches will not target all cell types equally. For example, studies in non-human primates have demonstrated that intravenous administration of AAV9 in juvenile non-human primates predominately transduces glia 21,37 while direct administration into the cerebral spinal fluid (CSF) improves delivery to neurons 38 (34). Our results suggest that maximizing neuronal correction will be essential to develop a treatment that improves functional outcomes in CLN3 disease.…”
Section: Discussionmentioning
confidence: 99%
“…While direct IP AAV delivery is highly efficient and well tolerated, it requires complex surgeries and in diseases like leukodystrophies that affect large brain areas a trade-off between surgical risk and number of injection-sites is required. Consequently, alternative delivery routes were investigated and following ICV injection, AAV8 and AAV9 were identified as the superior serotypes crossing the CBB, while AAV4 appeared favorable when exclusively targeting the ependymal cell layer ( Davidson et al, 2000 ; Chakrabarty et al, 2013 ; Bey et al, 2020 ). Comparison of 12 rAAV vectors for transgene expression in the CNS following IV revealed that particularly AAV7, AAV8, AAV9, AAV.rh8, AAV.rh10, AAV.rh39 and AAV.rh43 crossed the BBB ( Gray et al, 2013 ; Samaranch et al, 2013 ; Yang et al, 2014 ).…”
Section: The Evolving Adeno-associated Viral Vector Toolkitmentioning
confidence: 99%
“…For CNS- in vivo GT (i.e., direct introduction of the therapeutic vector into the CNS), AAVs have emerged as the safest vector and are the most commonly used ( Kantor et al, 2014 ), allowing various routes of administration, with specific targeting capacities depending on the capsid choices, stable transgene expression in postmitotic cells, low immunogenicity and low risk of toxicity or insertional mutagenesis. The vector can be delivered directly into the brain (intracerebral) or into the CSF (intrathecal, intracerebroventricular, or intracisternal) ( Bey et al, 2020 ). More recently, new serotypes of AAV have been shown to target the CNS after intravenous administration (in this case the vector has to cross the BBB), AAV9 and AAVrh10 being the most frequently used serotypes in clinical practice, due to their high capacity to transduce neural cells ( Cearley et al, 2008 ; Piguet et al, 2017 ; Bey et al, 2020 ) and some ability to cross the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…The vector can be delivered directly into the brain (intracerebral) or into the CSF (intrathecal, intracerebroventricular, or intracisternal) ( Bey et al, 2020 ). More recently, new serotypes of AAV have been shown to target the CNS after intravenous administration (in this case the vector has to cross the BBB), AAV9 and AAVrh10 being the most frequently used serotypes in clinical practice, due to their high capacity to transduce neural cells ( Cearley et al, 2008 ; Piguet et al, 2017 ; Bey et al, 2020 ) and some ability to cross the BBB. More recently, new AAV serotypes have been engineered with high tropism for the CNS after intravenous administration ( Li and Samulski, 2020 ).…”
Section: Introductionmentioning
confidence: 99%